Emergence of Ceftazidime/Avibactam and Tigecycline Resistance in Carbapenem-Resistant Klebsiella pneumoniae Due to In-Host Microevolution - Han, Xinhong; Shi, Qiucheng; Mao, Yihan; Quan, Jingjing; Zhang, Ping; Lan, Peng; Jiang, Yan; Zhao, Dongdong; Wu, Xueqing; Hua, Xiaoting; Yu, Yunsong (Frontiers in Cellular and Infection Microbiology, 2021)
Klebsiella pneumoniae can cause both hospital- and community-acquired clinical infections. Last-line antibiotics against carbapenem-resistant K. pneumoniae (CRKP), such as ceftazidime/avibactam (CZA) and tigecycline (TGC), remain limited as treatment choices. This study aimed to investigate the mechanisms by which CRKP acquires CZA and TGC resistance in vivo under β-lactam antibiotic and TGC exposure. Three CRKP strains (XDX16, XDX31 and XDX51) were consecutively isolated from an inpatient with a urinary tract infection in two months. PFGE and MLST showed that these strains were closely related and belonged to sequence type (ST) 4496, which is a novel ST closely related to ST11. Compared to XDX16 and XDX31, XDX51 developed CZA and TGC resistance. Sequencing showed that double copies of blaKPC-2 were located on a 108 kb IncFII plasmid, increasing blaKPC-2 expression in XDX51. In addition, ramR was interrupted by Insertion sequence (IS) Kpn14 in XDX51, with this strain exhibiting upregulation of ramA, acrA and acrB expression compared with XDX16 and XDX31. Furthermore, LPS analysis suggested that the O-antigen in XDX51 was defective due to ISKpn26 insertion in the rhamnosyl transferase gene wbbL, which slightly reduced TGC susceptibility. In brief, CZA resistance was caused mainly by blaKPC-2 duplication, and TGC resistance was caused by ramR inactivation with additional LPS changes due to IS element insertion in wbbL. Notably, CRKP developed TGC and CZA resistance within one month under TGC and β-lactam treatment without exposure to CZA. The CRKP clone ST4496 has the ability to evolve CZA and TGC resistance rapidly, posing a potential threat to inpatients during antibiotic treatment.